Engaging Copper(III) Corrole as an Electron Acceptor: Photoinduced Charge Separation in Zinc Porphyrin–Copper Corrole Donor–Acceptor Conjugates. Issue 4 (30th November 2015) - Ngo, Thien H.; Zieba, David; Webre, Whitney A.; Lim, Gary N.; Karr, Paul A.; Kord, Scheghajegh; Jin, Shangbin; Ariga, Katsuhiko; Galli, Marzia; Goldup, Steve; Hill, Jonathan P.; D'Souza, Francis
Abstract: An electron‐deficient copper(III) corrole was utilized for the construction of donor–acceptor conjugates with zinc(II) porphyrin (ZnP) as a singlet excited state electron donor, and the occurrence of photoinduced charge separation was demonstrated by using transient pump–probe spectroscopic techniques. In these conjugates, the number of copper corrole units was varied from 1 to 2 or 4 units while maintaining a single ZnP entity to observe the effect of corrole multiplicity in facilitating the charge‐separation process. The conjugates and control compounds were electrochemically and spectroelectrochemically characterized. Computational studies revealed ground state geometries of the compounds and the electron‐deficient nature of the copper(III) corrole. An energy level diagram was established to predict the photochemical events by using optical, emission, electrochemical, and computational data. The occurrence of charge separation from singlet excited zinc porphyrin and charge recombination to yield directly the ground state species were evident from the diagram. Femtosecond transient absorption spectroscopy studies provided spectral evidence of charge separation in the form of the zinc porphyrin radical cation and copper(II) corrole species as products. Rates of charge separation in the conjugates were found to be of the order of 10 10 s −1 and increased with increasing multiplicity of copper(III) corrole entities. The present study demonstrates the importance of copper(III) corrole as an electron acceptor in building model photosynthetic systems. Abstract : Donor–acceptor conjugates based on zinc porphyrin as the electron donor and copper(III) corrole as the electron acceptor have been successfully prepared with outstanding yields. Electrochemical and computational studies revealed the electron‐deficient nature of copper(III) corrole, leading to phenomena of photoinduced electron transfer from the singlet excited zinc porphyrin to copper corrole, as demonstrated by femtosecond transient spectroscopy.